2023
DOI: 10.3390/jcm12082753
|View full text |Cite
|
Sign up to set email alerts
|

Can Immunoexpression of Cancer Stem Cell Markers Prognosticate Tongue Squamous Cell Carcinoma? A Systematic Review and Meta-Analysis

Abstract: The objective was to evaluate the association of the immunoexpression of cancer stem cell (CSC) markers with clinicopathological and survival outcomes in tongue squamous cell carcinoma (TSCC) patients. This systematic review and meta-analysis [PROSPERO (CRD42021226791)] included observational studies that compared the association of clinicopathological and survival outcomes with CSC immunoexpression in TSCC patients. Pooled odds ratios (ORs) and hazard ratios (HRs) with 95% confidence intervals (CI) were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…The disease often presents at an advanced stage, limiting curative treatment options and leading to high mortality rates. Therefore, identifying new prognostic biomarkers that can accurately predict disease outcomes and guide treatment decisions, is crucial (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…The disease often presents at an advanced stage, limiting curative treatment options and leading to high mortality rates. Therefore, identifying new prognostic biomarkers that can accurately predict disease outcomes and guide treatment decisions, is crucial (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the paper proposes the future perspective of reversing immune evasion via epigenetic targeted therapies of even exploiting genomic events, which may prove essential in improving prognosis and survival in these patients. Chaudhury et al showed that measuring the expression of cancer stem cells in tongue SCC can yield relevant diagnostic data in terms of tumor size, histopathological grading, cancer dissemination, and mortality [ 14 ]. Additionally, in another recent paper, more attention was brought to the understanding of cellular signaling pathways involved in the carcinogenetic process of BCC.…”
mentioning
confidence: 99%